TubeSpam: filtragem automática de comentários indesejados postados no YouTube - Alberto, Túlio Casagrande (Universidade Federal de São Carlos, 2017)
YouTube has become an important video sharing platform. Several users regularly produce video content and make this task their main livelihood. However, such success is also drawing the attention of malicious users propagating undesired comments and videos, looking for self-promotion or disseminating malicious links which may have malwares and viruses. Since YouTube offers limited tools for blocking spam, the volume of such messages is shockingly increasing and harming users and channels owners. In addition to the problem being naturally online, comment spam filtering on YouTube is different than the traditional email spam filtering, since the messages are very short and often rife with spelling errors, slangs, symbols and abbreviations. This manuscript presents a performance evaluation of traditional online classification methods, aided by lexical normalization and semantic indexing techniques when applied to automatic filter YouTube comment spam. It was also evaluated the performance of MDLText, a promising text classification method based on the minimum description length principle. The statistical analysis of the results indicates that MDLText, Passive-Aggressive, Naïve Bayes, MDL and Online Gradient Descent obtained statistically equivalent performances. The results also indicate that the lexical normalization and semantic indexing techniques are effective to be applied to the problem. Based on the results, it is proposed and designed TubeSpam, an online tool to automatic filter undesired comments posted on YouTube.
TubeSpam: automatic undesired comments filtering on YouTube
Keywords: Youtube (Recurso eletrônico); Aprendizado do computador; Spam (Mensagens eletrônicas); Spam (Electronic mail); Machine learning; Youtube (Recurso eletrônico); Comentários indesejados; Undesired comments; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO